Expression of tenascin in lymphocytic autoimmune thyroiditis. - Back, W (1997)
AIMS: To study the distribution of tenascin by immunocytochemistry in autoimmune diseases of the thyroid. METHODS: Thyroids from patients with inflammatory lesions of the thyroid (lymphocytic thyroiditis Hashimoto, Grave's disease, thyroiditis DeQuervain) were studied by immunocytochemistry using antibodies against tenascin, collagen III, and collagen IV. RESULTS: In autoimmune lymphocytic thyroiditis Hashimoto there was a characteristic corona-like staining pattern of tenascin around all activated lymph follicles with germinal centres. This staining pattern contrasted with the immunoreactions for collagen III and IV, which were not enhanced in the perilymphofollicular interstitium. In cases of thyroiditis DeQuervain the areas of early and ongoing fibrosis showed some diffuse staining for tenascin and for collagen III. Enhanced diffuse immunostaining for collagen IV in the perivascular and interfollicular interstitium was present in cases of Grave's disease. In Grave's disease no characteristic immunoreaction was detectable for tenascin. CONCLUSIONS: The corona-like expression of tenascin around lymphofollicular infiltrates is distinctive of cases of lymphocytic thyroiditis. A similar staining pattern for tenascin has been reported in lymphoid hyperplasia of the thymus associated with myasthenia gravis, another autoimmunological disorder. There are good arguments that the activation and infiltration of lymph follicles in the thyroid during the course of autoimmune diseases lead to stimulation and activation of the surrounding mesenchyme producing tenascin as part of the extracellular matrix.